The Clinopathological and Prognostic Significance of SPOCK1 in Gynecological Cancers: A Bioinformatics Based Analysis - Enes Karaman; Fatih Yay; Durmus Ayan; Ergul Bayram; Sefa Erturk (Biology)
Background: Sparc/osteonectin, cwcv, and kazal-like domains proteoglycan 1 (SPOCK1) is an oncogene that promotes tumor formation and progression in certain types of cancer and is associated with poor survival rates. However, there is limited information on the importance of SPOCK1 in gynecological cancers in the literature. The aim of this study was to explore the role of SPOCK1 in ovarian serous cystadenocarcinoma (OV), cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC), and uterine corpus endometrial carcinomas (UCEC). Methods: The data used in this study were obtained from the GEPIA2, TCGA, Kaplan–Meier Plotter, GeneMANIA, UALCAN, cBioPortal, and TIMER databases. Overall survival (OS) and relapse-free survival (RFS) rates were evaluated by Kaplan–Meier survival analysis. Spearman’s rho and statistical significance values were obtained for the correlation between SPOCK1 expression and tumor infiltration by different immune cells. Results: Lower SPOCK1 gene expression was observed in CESC and UCEC compared to normal tissue (p < 0.05), but the OV did not differ significantly (p > 0.05). In OV, SPOCK1 gene expression was solely linked to age; in CESC, it was linked to age, stage, weight, and histology; and in UCEC, it was linked to age, stage, weight, and menopausal status. Conclusions:SPOCK1 gene expression in UCEC showed weak positive correlations with CD8+ T cells and weak negative correlations with CD4+ T cells. SPOCK1 may be a potential prognostic and therapeutic target for gynecological cancers.